Real-time ship detection and classification application framework based on airborne SAR image - Miao Weixing; Wang Xiaolong; Li Zhiyong; Yang Song; Zhang Xin; Ji Xinning (Dianzi Jishu Yingyong, 2022)
Synthetic aperture radar(SAR) is widely used in military-reconnaissance, ocean monitoring, disaster emergency assessment and other applications. Among them, ship detection and classification is an important ocean application. Due to the special imaging mechanism, the target features in SAR images are always changeable, which leads to the slow progress of target classification based on SAR images. In recent years, airborne SAR system has developed rapidly due to its real-time and convenience in deployment, and there is a strong demand for ship detection and classification based on airborne SAR images, especially for real-time detection and classification application. Focusing on this issue, a real-time application framework for ship detection and classification based on airborne SAR images is discussed and constructed, and the key processes and methods in engineering application are illustrated. In addition, its development trend combined with the artificial intelligence technology is also prospected.